MODERN METHODS OF TEACHING VOCABULARY IN THE CLASSROOM - Salikhova Nasiba Ibadullayevna (Galaxy International Interdisciplinary Research Journal, 2022)
In this section we’ll look at various techniques for presenting and, to a lesser degree, practicing vocabulary. It is important to realize that a good teacher will not rely on just one of these techniques, but will use a combination. Different techniques are appropriate for different vocabulary items and also for different types of learner. As you read through the different techniques, try to think what words would be best taught using the technique and for which words the technique would probably not work very well.